Effect of Fermentation Time on the Nutritional Composition of Soybean-Based Yoghurt: A Review - Oluwakemisola, Daramola Precious (Darul Yasin Al Sys, 2025)
The rising demand for plant-based dairy alternatives has heightened the need to optimize production processes for products such as soybean-based yoghurt. Fermentation time is a key determinant of the product’s nutritional profile, sensory attributes, and functional properties. This review synthesizes recent peer-reviewed studies to examine the effects of varying fermentation durations on protein digestibility, allergenicity reduction, carbohydrate transformation, fatty acid composition, mineral bioavailability, vitamin retention, and the formation of bioactive compounds. Findings suggest that medium fermentation durations (8–24 hours) generally offer the best balance between nutritional enhancement and probiotic viability. Longer fermentation periods can further improve phytate degradation and the conversion of isoflavone glycosides into more bioavailable aglycones, though they may also lead to decreased vitamin stability and undesirable acidification. These changes have important health implications, including improved protein digestibility, enhanced gastrointestinal health through probiotic enrichment, and increased suitability for lactose-intolerant and vegan consumers. However, research gaps persist, particularly in long-term storage stability, standardization of fermentation protocols, and the integration of fortification strategies. Future research should explore advanced microbial strain selection, enzyme-assisted fermentation, and metabolomic profiling to maximize nutritional and functional outcomes. This review offers practical insights for industry practitioners and researchers aiming to improve the quality and health benefits of soybean-based yoghurt.